Nurses' and physicians' attitudes toward physician-nurse collaboration in private hospital critical care units. - Le Roux, Lynn (My University, 2014)
In the setting of the critical care unit, the nurse is caring for the critically ill patients and is the care giver who is present at the bedside for 24 hours. The nurse comes into contact with all other disciplines attending to the patient and is thus often the common link in the multidisciplinary team. It is therefore essential that there is effective collaboration between the physician and the nursing practitioner.With the world-wide shortage of skilled nurses worsening, it is imperative that we look at a means of retaining our current nursing personnel and attracting new nurses into the profession. Many studies examining the relationship between a healthy work environment and the retention of nurses have rated collaboration as a key aspect. The setting for this study was five critical care units within the private health care sector. The study investigated both nurses’ and physicians’ attitudes towards collaboration in critical care units, as well as identifying factors which facilitate and constrain effective physician-nurse collaboration. Recommendations for enhancing collaboration within the critical care unit were explored. In this study a non-experimental descriptive design was be used. The Jefferson Scale of Attitudes toward Physician-Nurse Collaboration, a 15 statement Likert scale, was utilized to collect data from both the nurses and the physicians. The data was analysed using factor analysis and descriptive statistics. The results showed that nurses had a slightly more positive attitude toward collaboration as compared to the physicians, however the difference in the overall scores was not statistically significant.
Keywords: Critical Care; Patient Care Team